2002
DOI: 10.2989/16085906.2002.9626550
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS in South Africa: caring for vulnerable children

Abstract: South Africa currently has the fastest growing HIV/AIDS pandemic in the world. Efforts to manage the plight of children affected by HIV/AIDS have however been thwarted by two ubiquitous factors-poverty and inefficient state services. Caregivers, who are generally not public advocates for children's rights, disguise the state's negligence to respect, fulfill and protect children's rights. This paper suggests that the caring for HIV/AIDS affected children in South Africa needs to go beyond looking for willing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…This is supported by what others have found in Malawi and South Africa [20,24]. However, we identified several important differences in institutional, family- and community-based care environments with respect to their ability to uphold children’s rights and provide basic material needs, while identifying opportunities to strengthen family-based orphan care.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is supported by what others have found in Malawi and South Africa [20,24]. However, we identified several important differences in institutional, family- and community-based care environments with respect to their ability to uphold children’s rights and provide basic material needs, while identifying opportunities to strengthen family-based orphan care.…”
Section: Discussionsupporting
confidence: 82%
“…Community-based care refers to support programs administered by non-governmental organizations, religious groups, or community-based organizations (CBO’s) that typically enable children to remain in family-based care environments [20,23]. However, there are limited descriptions of these different models in the literature [20,24] or data on their resources, ability to provide basic needs, and protect the rights of orphaned and separated children. UNICEF and others have said that institutional care is not a viable solution and have recommended that countries move toward the de-institutionalization of orphaned children [6,25-27].…”
Section: Introductionmentioning
confidence: 99%
“…There is little empirical research on the experiences of children orphaned by AIDS in South Africa. Research is urgently needed on the impact of AIDS on children's physical and psychological well-being, and suitable programmes and policies must be both developed and evaluated (Walker, Reid and Cornell 2004;Loening-Voysey 2002). A study of caretakers (adult women) of orphaned HIV-infected children in Uganda found that caretaker worries centred on the health of the child, poverty (not having enough money to buy food, medicines, or paying school fees), and fearing the early death of the child (Brouwer et al 2000).…”
Section: Childrenmentioning
confidence: 99%
“…We need to go beyond merely identifying suitable and willing members in the community to take on the responsibility of caring for children affected by HIV/AIDS in South Africa (Sewpaul 2001;Loening-Voysey 2002). Many social workers in non-profit organisations (NPOs) are concerned about the state's expectations of services they must provide to those affected by HIV/AIDS, particularly since NPOs are so severely under-funded.…”
Section: Developmental Approachmentioning
confidence: 99%
“…Care in orphanages has been deemed expensive and cost ineffective [9], often resulting in worse outcomes for children due to high child-to-staff ratios, lack of social bonding and life skills, and stigma [8]. Although care by biological relatives is preferred, families in high prevalence, low resource communities have become overwhelmed by the numbers and needs of orphans, and remaining HIV-infected parents or other caregivers may themselves die before the orphan reaches adulthood.…”
Section: Introductionmentioning
confidence: 99%